Automatic System of Sound and Light Intensity for Swiftlet House - Muhammad Ragil Prayoga; Nursobah; Siti Lailiyah (TEPIAN, 2023)
In cultivating swiftlet nests, some swiftlet breeders still find it difficult to summon sounds and control the intensity of light in swiftlet houses. As for the bird calling technique by playing the audio of the swiftlet without having to be heard at any time and there is also a certain hour, an automatic time system is made so that the on/off audio swiftlet process can be properly organized and also the intensity of light entering the swiftlet house is too bright, so breeders close the ventilation holes with insulation or wood, so the system will be made to control light intensity by using automatic opening or closing of curtains/windows, where when the swiftlet house is bright, the curtain closes, while when the light of the swiftlet house is dark, the curtain opens. RTC DS3231 and LDR sensor which functions as a detector of sound time and light intensity, the NodeMCU ESP8266 microcontroller which functions as a data processor so that results can be displayed on the LCD. This research was conducted in stopover Village, stopover District, West Kutai Regency. Data collection methods used are literature study, interviews, and observation. While the system development method used is Prototype. As well as supporting software used by the Arduino Integrated Development Environment. While the system development method used is Prototype. As well as supporting software used by the Arduino Integrated Development Environment. While the system development method used is Prototype. As well as supporting software used by the Arduino Integrated Development Environment.